LIGHTWEIGHT DESIGN FOR OVERHAUL TOOLING SUPPORT SEAT BASED ON TOPOLOGY OPTIMIZATION AND SIX SIGMA ROBUSTNESS - WANG ZiNing; WU JianJun; XIANG JianMing; WANG BaiSong; JIN YingQi (Jixie qiangdu)
In order to give full play to the lightweight potential of the tread braking unit（ TBU） overhaul tooling support seat and improve the reliability and robustness of the optimization design,an optimization strategy composed of topology optimization and 6σrobustness optimization was proposed. Support seat’s topology structures was extracted based on topology optimization with variable density method. The response surface model was established based on the central composite design method and the finite element numerical simulation technique. The support seat’s 6σ robustness optimization design model was established based on this model. The sequential quadratic programming method was adopted to solve this optimization problem.The reliabilities of the optimization results were obtained with the mean value first order and second moment method,and were transformed into corresponding σlevels. The results show that reliability of the design variables,strength and stiffness are all 1,reaching eight sigma level,the support seat’s weight is reduced by 67. 0% and the lightweight effect is remarkable; compared with the support seat’s traditional deterministic optimization design after topology optimization,this method enhances the strength and stiffness of the support seat,meanwhile,improves the reliability of the optimization design,the robustness of the strength,the robustness of the stiffness and the consistency of the weight. So the proposed optimization strategy is proved to be efficient.